Nodular Fasciitis Complicating a Staged Surgical Excision of Dermatofibrosarcoma Protuberans. (27th November 2016) - Malone, C. Helen; Goodwin, Brandon; Wagner, Richard F.; Resto, Vicente; Kelly, Brent
Abstract : Dermatofibrosarcoma protuberans (DFSP) is an unusual spindle cell tumor with a high rate of local recurrence with traditional excision. Fortunately, Mohs micrographic surgery yields excellent cure rates for this neoplasm due to contiguous tumor spread and meticulous tumor mapping and margin analysis. We present the unique case of a patient treated with a modified Mohs technique with an analysis of the final margin with permanent sections, who developed a spindle cell neoplasm in the margins of her second stage excision consistent with nodular fasciitis. Distinguishing residual DFSP from a benign reactive process was an essential and challenging component of this patient's management.